Features of applying russian experience in preparing qualified china athletes in mini-football - Si Debu; Zhang Xiaoming; Zhang Jun; Polishkis M.M. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of the use of Russian experience in the preparation of qualified Chinese athletes in mini-football (futsal). Methods and structure of the study. A survey was conducted of coaches working with futsal student teams of the Russian University of Sports "GTSOLIFK" (Moscow, Russia), the Mongolia Technological University (Hohhot, China), Beijing Sports University and Peking University (Beijing, China). Results and conclusions. The effectiveness of training qualified Chinese athletes in mini-football (futsal) is determined by the use of advanced approaches to organizing the structure and content of the training process, which is based on a variety of training tools. The Russian system of training qualified athletes in mini-football (futsal), over a long period of testing scientific, theoretical and practical approaches to organizing the training process, has shown its high efficiency, which is confirmed by the results of national and club teams at competitions of various ranks. Thus, it is advisable to substantiate the specifics of using Russian experience in training qualified Chinese athletes in mini-football (futsal).